TINGKAT KESEGARAN JASMANI PADA SISWA SMP NEGERI 2 KREMBUNG DAN SMP NEGERI 2 SIDOARJO - Widodo, Bayu Sri; Kusnanik, Nining Widyah (Jurnal Prestasi Olahraga, 2013)
Education is conscious and deliberate effort to create a learning environment and the learning process so that learners are actively developing the potential for him to have self control, personality, intelligence, noble character, and skill needed him and the community. There are several kinds of education one of them is physical education. Physical education can be maximized if a person has a good level of physical fitness. Purpose of this study was to determine the level of physical fitness of SMPN 2 Krembung and SMPN 2 Sidoarjo and to know which of two schools that have a good level of physical fitness.Type of this research is quantitative research using descriptive method of analysis. A sample of students who are male and female of student class VIII were extracted using cluster random sampling techniques so as to get 25 students in each school. Researcher used a 5 item test TKJI tests conducted sequentially.The results of the study were an average of SMPN 2 Krembung TKJI is running 50 meters averaging 7:37? seconds male and 8:8? seconds female. Bend your elbows hanging on average 4 times male and 32:13 seconds female. Lie sat down on everage 41.26 times male and 27.6 times female. Vertical jump an average 41.26 cm and 27.8 cm female. 1000 meter male run average 4 minutes 58 seconds and 800 meter female 4 minutes and 41 seconds. SMP 2 Sidoarjo is running 50 meters averaging 8:08? seconds male and 8.51? seconds female. Bend your elbows hanging on average 4.48 times male and 32:24 seconds female. Lie sat down on everage 37.26 times male and 33.5 times female. Vertical jump an average 41.33 cm and 36.4 cm female. 1000 meter male run average 5 minutes 18 seconds and 800 meter female 5 minutes and 41 seconds.Conclusion average physical fitness level best category owned by the son of SMP Negeri 2 Krembung. While the category of best daughter owned by SMP Negeri 2 Sidoarjo.